2019
DOI: 10.1108/ijoem-03-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Risk governance and bank profitability in ASEAN-5: a comparative and empirical study

Abstract: Purpose The purpose of this paper is to highlight the disparity between the disclosures of risk governance (RGOV) categories, namely, structures both at the board and management level, and RGOV practices among five of the Association of Southeast Asian Nations (ASEAN-5) countries. Furthermore, this paper investigates the effects of RGOV and its categories on return on assets (ROA). Design/methodology/approach Using 285 ASEAN-5 bank-year observations comprising hand-collected data for the period of 2010–2014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Some studies of the Chinese banking market have related bank competition with financing constraints (Zhang, Zhang et al, 2019). Bank profitability has also been linked with risk governance (Karyani et al, 2019), and efficiency has been linked with lending (Anwar et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies of the Chinese banking market have related bank competition with financing constraints (Zhang, Zhang et al, 2019). Bank profitability has also been linked with risk governance (Karyani et al, 2019), and efficiency has been linked with lending (Anwar et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, most risk management committees did not have sufficient independent and financially competent members. Also, Karyani et al (2019) have found no effects of risk governance in terms of board-level risk governance structure and risk management practice on ROA. However, the authors have documented a significant negative effect of the management-level risk governance structure on the sample bank ROA.…”
Section: Related Literaturementioning
confidence: 91%
“…The endogeneity issue in this research is considered by ensuring the possibility of an antipodal effect on whether ERM invigorates corporate governance and Sharia compliance (Karyani et al, 2019). The results of the endogeneity test in Table 5.…”
Section: Endogeneity Testmentioning
confidence: 99%
“…Indonesia itself was affected by the Asian financial crisis on 1997-1998, thus resulted in the provisions concerning bank health by Banking regulator and supervisors. Howbeit, it is also a necessity for the banking industry to ordain risk management to finesse any potential risk that may ascend (Karyani et al, 2019). The application of risk management is one of the mechanisms that must be applied in governance in order to control management activities so as to minimize the occurrence of fraud practices.…”
Section: Introductionmentioning
confidence: 99%